Magnetic surfaces of an l=4 stellarator in regard to helical coil angular size and method of conductor turn packing - Kotenko, V.G. (Вопросы атомной науки и техники, 2009)
Numerical studies were undertaken to elucidate the influence of the helical-coil finite angular size on l=4 stellarator magnetic surface characteristics. The calculations are applied to the closed magnetic surface configuration removed from the torus surface. The magnetic surface characteristics did not change significantly in comparison with ideal model of the l=4 stellarator magnetic system.